Polityka rachunkowości w jednostkach budżetowych - Rudnicka, Bożena (The Politics of Accounting in the State-Budget-Financed Entity, 2005)
The state-budget-financed entity is obliged to possess documentation on the adopted accounting principles that take into consideration both general regulations as set forth in the Accounting Act and specific regulations pertaining exclusively to state-financed entities. The regulations substantially constrain the entity in its choice of the principles of the assets and liabilities valuation as well as the format of corporate set of accounts. This is determined by the entity's business activity and necessity of providing the aforementioned entities with uniform accounting principles, first of all with a view to an efficient planning and controlling of an execution of the budget (through a uniform budget reporting system).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 373-378